Grundlagen of Legal Responsibility and Guaranteeing the Efficacy of Measures in Compliance with European Human Rights Standards - Nataliia Zahrebelna; Andrii Dubovoi; Oleksandr Vashchuk; Serhii Sadovyi; Alla Pyshna (Yustisia, 2024)
The study aims to analyze effective human rights protection by clarifying the concept of legal liability from the point of view of the EU legislation and case law on human rights. Ensuring justice, freedom, and equality before the law is important. Ukraine is committed to EU integration; therefore, adapting Ukrainian legislation to European standards is a key step in this process. The study focuses on determining the need for and ways of adapting the Ukrainian legal framework to European standards. As a result of the study, The European Union (EU) plays a crucial role in Ukraine's foreign and integration policy, emphasizing the need to harmonize legislation with European standards. Legal liability is crucial in modern legal doctrine, ensuring the rule of law, guaranteeing rights, and protecting interests. Ukraine should learn best practices from the EU, such as Germany's "judicial autonomy" principle, to strengthen its independence. The EU also promotes transparency in appointments and careers, fighting corruption through anti-corruption bodies and financial control. Ukraine should also study and implement effective administrative liability systems, such as those used by France and Spain, to improve internal control and respond effectively to violations.